(untitled) (Third Sector Social Economic Review, 2019)
FoMO, which means the fear of abducting the developments, has a place in social media marketing with the effect of social media on people and has a serious reinforcement power. Individuals share constantly their eatings, wearings, visited places, social and cultural activities, etc. from social media channels such as Facebook, Twitter, Instagram, Foursquare, Swarm, etc. Their sharing has created fear of missing out and the need to satisfy various pleasures by their followers. This is one of the most important factors driving the businesses that want to increase sales figures with the followers’ pleasure satisfaction by using FoMO, to social media marketing. In the study, fear of missing out is associated with FoMO and the infinite pleasure satisfaction is associated with Hedonic Consumption. In order to obtain the relationship, an online survey was applied through social media. The data obtained were classified and analyzed using SPSS 22 statistical package program.